IV and V grade arteriovenous Malformations: A multicenter surgical experience. Use of multiple grading system to predict surgical risk. (October 2022) - Cannizzaro, Delia; Scibilia, Antonino; Frio, Federico; Zaed, Ismail; Safa, Adrian; Cirillo, Luigi; Sturiale, Carmelo; Cardia, Andrea; Bortolotti, Carlo
Highlights: Cerebral Arteriovenous Malformations (cAVMs) represent a rare cerebral disease characterized by significant rate of morbidity and mortality mainly related to the hemorrhagic propensity. The aim of the present study is to report a multicenter surgical experience in the treatment of IV and V grade AVMs, in order to simplify the interpretation of currently used scales and improve management strategies for these vascular high-grade lesions. The pre-operative mRS was a factor influencing clinical outcome, as well as the number of bleedings preceding the treatment, age, and nidus characteristics. S-M IV, L-Y 3 and S-M supp 7 scores were associated with good outcome. Surgical management for high-grade AVMs should be considered in highly selected patients with repeated bleeding or disabling symptoms. Abstract: Objective: The aim of our study is to report a multicenter experience in the treatment of IV and V grade arteriovenous malformations (AVMs) and to apply commonly used grading scales for surgical risk assessment for these vascular high-grade lesions. Methods: Between January 2015 and December 2019, a retrospective study was conducted to identify patients undergoing microsurgical intervention for cAVMs at two Italian centers specialized in the treatment of vascular pathologies. Data on patients with Spetzler-Martin IV and V and with a score equal or more than 7 according to Lawton-Young classification were collected. Ruptured AVMs at admission were subsequently classified according to the new proposed AVICH classification. Results: A total of 20 patients with high grade (IV and V) cAVMs were enrolled in the study and the average follow-up was 36.45 months. The outcome based on mRS was favorable in 65 % of cases. The pre-operative mRS was a factor influencing clinical outcome, as well as the number of bleedings preceding the treatment, age, and nidus characteristics. S-M IV, L-Y 3 and S-M supp 7 scores were associated with good outcome. Based on the AVICH classification, for ruptured cAVMs, having a score of 9 ore less was correlated to a postoperative mRS fewer or equal than 2. Conclusions: Surgical management for high-grade AVMs should be considered in highly selected patients with repeated bleeding or disabling symptoms. Classification systems provide an aid in selecting patients for surgery, also in grade IV and V. It is essential to establish common registers for the management of these complex vascular malformations.